Peran Pendidikan Lingkungan dalam Meningkatkan Kesadaran dan Tindakan Berkelanjutan di Sekolah Dasar - Ilham, Ahmad Januardi; Kusuma, Adila Tasya; Putri, Febby Rahma; Selsia, Bekhi (MASALIQ, 2023)
Environmental education has an important role to play in raising awareness and sustainable action in primary schools. This article aims to investigate the role of environmental education in influencing students' attitudes, knowledge, and behavior regarding environmental issues in elementary schools. A qualitative research approach was used to collect data through interviews, observation, and document analysis. The results of the study show that integrated environmental education with the elementary school curriculum can result in an increase in students' awareness of environmental issues that are relevant to their environment. In addition, students who receive good environmental education also show improvements in sustainable actions, such as reduced water and energy use, better waste management, and participation in environmental activities. Factors that influence the effectiveness of environmental education in primary schools include the role of trained teachers, the use of interesting learning methods, support from the school, and the involvement of parents and the community in supporting sustainable efforts in schools.